ANALYZING STUDENTS' READING COMPREHENSION ON DESCRIPTIVE TEXT AT SMP PANGERAN ANTASARI MEDAN - Br Sigalingging, Indy Corry Gabriela; Tampubolon, Jonris (ELT (English Language Teaching Prima Journal), 2024)
This research investigates the reading comprehension of descriptive texts among students at SMP Pangeran Antasari Medan. The study employs a descriptive research methodology to assess students' abilities to comprehend and analyze descriptive text. Data was collected through tests and interviews, targeting a specific class of 32 students. The results indicate a varied level of proficiency among students, with a significant number demonstrating excellent comprehension in multiple-choice tests while showing weaker performance in true/false assessments. The research identifies vocabulary and prior knowledge as key factors influencing reading comprehension. Interviews with teachers support these findings, highlighting differences in students' abilities based on their background and support systems. The study emphasizes the need for enhanced vocabulary learning and more effective reading strategies to improve comprehension skills.